Make a Match dalam Peningkatan Kosakata Bahasa Jerman - Dwi Yana Kahar; Laelah Azizah (Academic : Journal of Social and Educational Studies, 2024)
Abstract. The purpose of this study was to determine the Mastery increase of German vocabulary of grade XI students of SMA Negeri 14 Gowa through the Make A Match learning model. The purpose of this study is a classroomaction research which consists of two cycles. The purpose of this study was to determine the planning, implementation, observation, and reflection. The subjects in this study were class XI IPS 3 students of SMA Negeri 14 Gowa, totaling 36 people.. The data in this study consisted of two types, namely: quantitative data and qualitative data. Qualitative data were obtained through observation and quantitative data obtained through the Mastery increase of German vocabulary test at the end cycle I and cycle II. The average score the Mastery increase of German vocabulary obtained by students in the first cycle it was 65,6%, while in the second cycle it was 78,3%. These results indicate that the use of Make A Match learning model can increase the German vocabulary of grade XI students SMA Negeri 14 Gowa.  Keywords: Learning Model, Vocabulary, Make A Match.